PRODUÇÃO E CARACTERIZAÇÃO DE SCAFFOLDS ELETROFIADOS A PARTIR DE POLICAPROLACTONA/PLURONIC/HIDROXIAPATITA PARA APLICAÇÕES BIOMÉDICAS - RIBEIRO, LARISSA GULOGURSKI (2022)
Tissue engineering is currently being widely explored in various application branches. Among them, its use in medicine stands out regenerative, in a broad and versatile way, such as, for example, in the manufacture of micro and nanostructured bioactive materials, capazes de mimetizar a matriz extracelular e atuarem como curativos inteligentes em feridas crônicas. One of ways in which these materials are obtained is electrospinning, which allows the obtaining fibers in nanometric and micrometric scale, from a solution containing a volatile solvent and a polymer subjected to high stress. One of the polymers most used in the manufacture of these materials, and already approved by agencies of health, is polycaprolactone (PCL) because it is biodegradable and biocompatible. One problem in its characteristics is the hydrophobicity it presents, which can compromising the adhesion and proliferation of cells to the fibers. Such inconvenience can be resolved, for example, through the manufacture of polymeric blends and/or with the composite production. In this work, composites were produced from the blend polymeric PCL/F-127 with hydroxyapatite (HA) ceramic with a view to obtaining materials with bioactive properties to act as scaffolds in regeneration of living tissues in wounds. The PCL/F-127/HA composite was produced by the technique of electrospinning and characterized by different techniques: infrared spectroscopy, differential scanning calorimetry, thermogravimetry, electron microscopy by scanning and energy dispersion X-ray spectroscopy. The results showed that it was possible to obtain nano and micrometric fibers both from pure PCL, how much of the PCL blend with F-127 (PF) and the PF blend composite with particles of hydroxyapatite. Changes were noted in the polymeric chain and crystallinity of PCL both because of the electrospinning process and because of the addition of F-127. However, with the addition of hydroxyapatite there was a tendency to increase the crystallinity because it decreases the rate of evaporation of the solvent during the process of electrospinning. Tests performed on cultured human fibroblasts revealed that electrotrophied membranes have low cytotoxicity. Therefore, the materials developed in this work have the potential to be used in the future in biomedical applications.